INTEGRASI KARAKTER CINTA TANAH AIR MELALUI PEMBIASAAN PAGI BERBAHASA JAWA DI SDN PANDEANLAMPER 01 SEMARANG - Sabila, Fika Ayuni; Azizah, Mira; Paryati, Paryati (Universitas Negeri Medan, 2024)
Abstract: This research aims to analyze the morning habit of speaking Javanese in building the character of love for the country, which aims to ensure that children do not forget their regional culture and maintain their original culture. In this research, researchers used qualitative research methods by collecting data through observation and interviews at SDN Pandeanlamper 01 Semarang. The results of the research show that morning lessons in Javanese are carried out regularly and involve the entire school community. This morning Javanese language habituation activity includes using Javanese sentences in daily conversations and singing Javanese songs. This morning habituation in Javanese language aims to instill the character value of love for the country, through this habituation the children continue to know their culture, namely the Javanese language. It is hoped that instilling the values of love for one's country can preserve Indonesian culture. Morning practice in elementary school is the first step in building good character in students. Keyword: Character, Love for the Motherland, Morning Habits in Javanese Abstrak: Penelitian ini bertujuan untuk menganalisis pembiasaan pagi Berbahasa Jawa dalam membangun karakter cinta tanah air yang bertujuan agar anak tidak melupakan budaya daerahnya dan mempertahankan budaya asli. Pada penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan pengumpulan data melalui observasi dan wawancara di SDN Pandeanlamper 01 Semarang. Hasil penelitian menunjukkan bahwa pembiasaan pagi berbahasa jawa dilaksanakan secara rutin dan melibatkan seluruh warga sekolah. Kegiatan pembiasaan pagi berbahasa jawa ini meliputi kegiatan berkalimat dengan bahasa jawa dalam percakapan sehari-hari dan bernyanyi lagu bahasa jawa. Pembiasaan pagi berbahasa jawa ini bertujuan untuk menanamkan nilai karakter cinta tanah air, melalui pembiasan tersebut membuat anak tetap mengenal budaya mereka yaitu bahasa jawa. Penanaman nilai-nilai karakter cinta tanah air diharapkan dapat menjaga kelestarian budaya Indonesia. Pembiasaan pagi di sekolah dasar merupakan langkah awal dalam membangun karakter yang baik pada peserta didik.Kata Kunci: Karakter, Cinta Tanah Air, Pembiasaan Pagi Berbahasa Jawa